Exploring group work during Mandarin classes using Tuckman’s model / On Yee Min ... [et a.l] - On, Yee Min; Lim, Siew Mei; Teo, Ai Min; Ho, Wee Chee (UiTM Cawangan Johor, 2024)
Group work is commonly used to promote teamwork, problem-solving, and exchanging ideas and perspectives among group members. To explore how Malaysian students perceive the various stages of group work and investigate the relationship between all stages, quantitative research was conducted on 165 university students taking Mandarin as a Foreign Language course. The Tuckman's Model was implemented in this study. The study indicates that learners at the forming stage are more likely to assign specific roles to team members and try to define the goal and what tasks need to be accomplished. During the storming stage, where discussions take place, the findings show that learners agree with the statement that the team leader should be the one who tries to contribute to the task at hand. The norming stage demonstrates that learners tend to achieve harmony by avoiding conflict and accepting each other as team members. During the performing stage, learners agree that they got a lot of work done, they appear to perceive the interactions in the group as positive and cooperative, and they fully accept each other's strengths and weaknesses. The findings also indicate that various stages of group work are linked to one another in a constructive progression, revealing that these stages are not distinct from one another but rather interconnected in a positive progression. It can be helpful to gain awareness of these linkages to guide a group effectively.